Specific primers design based on the superoxide dismutase b gene for Trypanosoma cruzi as a screening tool: Validation method using strains from Colombia classified according to their discrete typing unit (2014)
ABSTRACT: Objective: To classify 21 new isolates of Trypanosoma cruzi (T. cruzi) according to the Discrete Typing Unit (DTU) which they belong to, as well as tune up a new pair of primers designed to detect the parasite in biological samples. Methods: Strains were isolated, DNA extracted, and classified by using three Polymerase Chain Reactions (PCR). Subsequently this DNA was used along with other isolates of various biological samples, for a new PCR using primers designed. Finally, the amplified fragments were sequenced. Results: It was observed the predominance of DTU I in Colombia, as well as the specificity of our primers for detection of T. cruzi, while no band was obtained when other species were used. Conclusions: This work reveals the genetic variability of 21 new isolates of T. cruzi in Colombia.Our primers confirmed their specificity for detecting the presence of T. cruzi.